2018
DOI: 10.1017/jfm.2018.709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of helicity on dissipation in homogeneous box turbulence

Abstract: The dimensionless dissipation coefficient β = εL/U 3 , where ε is the dissipation rate, U the root-mean-square velocity and L the characteristic scale of the largest flow structures, is an important characteristic of statistically stationary homogeneous turbulence. In studies of β, the external force is typically isotropic and large scale, and its helicity H f either zero or not measured. Here, we study the dependence of β on H f and find that it decreases β by up to 10% for both isotropic forces and shear flo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Under the influence of the second channel of helicity cascade, the small scales do not easily receive energy from large scales, and viscosity is not inclined to work well in near-dissipation regions. This conclusion is consistent with previous opinions that helicity can decrease the viscous dissipation of energy (Linkmann 2018).…”
Section: Roles Of the Dual Channels In The Energy Cascade Processsupporting
confidence: 94%
“…Under the influence of the second channel of helicity cascade, the small scales do not easily receive energy from large scales, and viscosity is not inclined to work well in near-dissipation regions. This conclusion is consistent with previous opinions that helicity can decrease the viscous dissipation of energy (Linkmann 2018).…”
Section: Roles Of the Dual Channels In The Energy Cascade Processsupporting
confidence: 94%
“…In fully developed turbulent flows, it is shown in Ishihara et al () and Djenidi et al () that the effective amount of kinetic energy dissipation, measured in terms of its dimensional evaluation ϵD=U03false/L0, tends to a constant close to 1/2 for a variety of laboratory and numerical experiments, in the forced case as well as for decaying flows provided their Taylor Reynolds numbers be sufficiently high, but there is also a marked deficiency, of the order of 10%, in the presence of nonzero helicity (Linkmann, ). The actual amount of dissipation (as opposed to that expected for a field composed of a superposition of linear waves interacting weakly) directly influences the overall atmospheric and oceanic energetic exchanges, and it can also modify conditions for acoustic transmission, as well as for deepwater drilling.…”
Section: The Bidirectional or Dual Cascades In Turbulencementioning
confidence: 99%
“…The constant C in this nonlinear contribution sets the asymptotic value of the normalized dissipation rate L/K 3/2 [11] and represents thereby the dissipative anomaly [12], i.e., a nonvanishing dissipation when the viscosity tends to zero. It is indeed observed that L/K 3/2 tends to a constant at high Reynolds numbers for a given flow [13], but its value can depend on the large-scale structure of the energetic scales [14], the presence of helicity [15], or the instationarity (as observed in Ref. [16] and explained in Ref.…”
Section: Linearly Forced Flowmentioning
confidence: 74%
“…[17]). Model 1 was rigorously derived as an upperbound for turbulent dissipation in the Navier-Stokes equations both for static forcing [18,19] and dynamic forcing [15]. The low Reynolds limit of Model 1 was shown to quite accurately describe the results of simulations and closure in references [10,14].…”
Section: Linearly Forced Flowmentioning
confidence: 99%